PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK (KAP), DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Siti Lutfiani; Arief Himmawan Dwi Nugroho (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
This study aims to examine and analyze the significance of the variables that influence audit delay in LQ-45 stock companies listed on the Indonesia Stock Exchange. This study used scientific methods, the population in this study were 52 LQ-45 stock companies listed on the IDX. The year range used in this study is 3 years, namely 2020-2022. The sampling technique was purposive sampling and a sample of 25 companies was obtained. The study used descriptive statistical tests, convergent validity tests, discriminant validity tests, composite reliability tests, Crobsh's Alpha tests, R-Square tests, Fit Model Results, Multicollinearity tests, Multiple linear regression analysis tests, and hypothesis testing with SMART PLS-4 as a processing application. research data. The results showed that the variable profitability and firm size had a significant positive effect. While the Solvency and Auditor Opinion has no significant negative effect, the size of the Public Accounting Firm (KAP) has a significant negative effect. The ability of the variable profitability, solvency, company size, size of the public accounting firm (KAP) and auditor opinion, in explaining audit delay of 12% is indicated by the adjusted R square of 0.120 while the remaining 88% is explained by other variables outside this research model.